Risk communication and community engagement in COVID-19: Fighting infodemics among non-governmental/community-based organizations in Africa - Silas O. Emovwodo; Sunkung Danso; Emmanuel M. Massay; Yahya M. Bah (AOSIS, 2022)
As the world battles the latest strain of the coronavirus known as COVID-19 characterized as a pandemic by the World Health Organization (WHO), "infodemics" - an excessive amount of (mostly untrue) information about the pandemic that makes it difficult to discern essential information - has been identified by the health body as one of the major obstacles to be tackled to win the war against the raging pandemic. In a bid to control spread of the virus, the WHO published a guideline on Risk Communication and Community Engagement (RCCE) to COVID-19, noting these responses are vital for containment. The COVID-19 pandemic is testing and stretching health systems and their ability to effectively communicate with their populations. Failure to communicate accurate public health facts could lead to losses of trust, reputation, economy, and lives. This paper turns its searchlight on nongovernmental and community-based organizations (NGOs and CBOs) in Africa, and how they handle infodemics in an information environment battling not just a health pandemic, but a hoax pandemic too. Methods: The study employed mixed method, with data drawn from Africanbased NGOs and CBOs via online questionnaire and interviews against the backdrop of the Situational Theory of Publics. Findings reveal, based on what NGO/CBO survey respondents report their local clients think, that many at the grassroots still do not believe COVID-19 is real, while others view it as government's scheme to embezzle funds. NGO/CBOs therefore look to WHO and Health Ministries for accurate information. It concludes that RCCE with the public and atrisk populations help reduce confusion and builds trust in the public health guidance community members can take thereby restricting the disease spread as an outcome of the RCCE approach.